2021
DOI: 10.1002/cssc.202101853
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Molecular Weight Changes during Technical Lignin Depolymerization by Operando Attenuated Total Reflectance Infrared Spectroscopy and Chemometrics

Abstract: Technical lignins are increasingly available at industrial scale, offering opportunities for valorization, such as by (partial) depolymerization. Any downstream lignin application requires careful tailoring of structural properties, such as molecular weight or functional group density, properties that are difficult to control or predict given the structure variability and recalcitrance of technical lignins. Online insight into changes in molecular weight (Mw), to gauge the extent of lignin depolymerization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Technical lignins are still not sufficiently utilized even though they hold considerable potential for production of renewable chemicals and materials. , The direct material usage is still hindered by a number of barriers, prominently by the lignin heterogeneity caused by a high molecular weight (MW) dispersity, various interunit linkages, and impurities. Fractionation of technical lignins by preparative size exclusion chromatography (SEC), solvent, or membrane fractionation has been revealed to provide narrower fractions of MW classes, which further showed enhanced performance in specific applications such as bio-based polyurethane foams or carbon fibers. ,, In particular, solvent fractionation, with multiple solvents in a certain order, classifies technical lignins in size . However, the solvent fractionation method, used for this work, in only acetone–water mixtures is much more process- and cost-efficient in regard to scale-up.…”
Section: Introductionmentioning
confidence: 99%
“…Technical lignins are still not sufficiently utilized even though they hold considerable potential for production of renewable chemicals and materials. , The direct material usage is still hindered by a number of barriers, prominently by the lignin heterogeneity caused by a high molecular weight (MW) dispersity, various interunit linkages, and impurities. Fractionation of technical lignins by preparative size exclusion chromatography (SEC), solvent, or membrane fractionation has been revealed to provide narrower fractions of MW classes, which further showed enhanced performance in specific applications such as bio-based polyurethane foams or carbon fibers. ,, In particular, solvent fractionation, with multiple solvents in a certain order, classifies technical lignins in size . However, the solvent fractionation method, used for this work, in only acetone–water mixtures is much more process- and cost-efficient in regard to scale-up.…”
Section: Introductionmentioning
confidence: 99%
“…52 In the process of isolating technical lignins, both the labile aryl-alkyl and b-O-4 bonds are most prone to cleavage. 53 This results in technical lignins having more condensed and variable structures than native lignin, and a wide variety in molecular weight (M w ). Mass average values (M w ) of 1000-15 000 g mol −1 for soda lignin, 1500-25 000 g mol −1 for Kra lignin, and 1000-150 000 g mol −1 for lignosulfonates have been reported, depending on botanical origin and process conditions.…”
Section: Structure and Composition Of Natural Ligninmentioning
confidence: 99%
“…GPC is commonly employed for the analysis of lignin degradation and the identification of average molar masses. It has also recently been demonstrated that it is possible to obtain information on molecular weight in real time during technical lignin depolymerization by combining operando attenuated total reflectance infrared (ATR‐IR) spectroscopy with chemometrics [86] . In the studies on oxidative depolymerization of technical lignins by heterogeneous catalysts, as summarized in Table 3, HPLC and GC separation coupled with FID, UV detection, refractive index, or MS detection were used in the majority of cases for the quantification of a few selected products that are commercially available as authentic standards.…”
Section: Oxidative Valorization Of Ligninmentioning
confidence: 99%